Teachers’ Perceptions and Experiences on Student Engagement in Nepali Secondary EFL Classrooms - Bhatt, Bhakta Raj (Far Western Journal of Education, 2025)
Pedagogy in English as foreign language situations has undergone a significant shift at present and receiving an increased attention of educators and scholars from worldwide that teaching strategies should ensure the involvement of students in learning activities. This qualitative research study aims to explore the perceptions and experiences of teachers on student engagement in secondary level EFL classrooms. Four English language teachers as research participants were purposively selected from public secondary schools of Kanchanpur district, Nepal. I employed narrative inquiry as a research method in which in-depth interview protocols were used as research tools to obtain the information. The findings of the study showed that English teachers at secondary level make efforts to employ student-focused teaching methods to promote student engagement in learning activities. The study also revealed that English teachers utilize student-centred techniques like group and pair work, conversation, project works, presentations, role-playing, spelling and quiz contests, etc., to engage students in learning. The study further revealed student motivation as crucial element of teaching that teachers employ promoting students’ learning through their active involvement. Likewise, this study revealed students’ poor base of English as the primary challenge, and other challenges like lack of infrastructural facility and ICT facilitated classes for language teaching-learning. The findings suggest that English teachers need to devise their teaching plans to improve students’ basic knowledge in English. They have to develop students’ confidence level providing extensive exposure to English so that they feel comfortable involving in learning activities.